1980
DOI: 10.1007/bf02876399
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical similarities among strains ofAureobasidium pullulans (de Bary) Arnaud

Abstract: Seventy-seven properties of Aureobasidium pullulans including utilization of various carbon sources, decomposition of the lignin-cellulose complex and the respective enzymes were checked in the present communication. According to these properties the group of 43 strains was separated in three parts, out of which two groups were found to belong to varieties A. pullulans var. pullulans and A. pullulans var. melanigenum. The third group formed a marginal part. The two varieties differed in numerous biochemical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Recent work by Manitchotpisit et al reported that most strains of A. pullulans in genetically diverse phylogenetic clades could produce PMLA. Ĉernáková et al found that A. pullulans could utilize a wide variety of carbon sources, such as d ‐xylose, lactose, sucrose, maltose, cellobiose, inulin, soluble starch, nonglycosidic substrates, etc. So far, there have been very limited publications available regarding the effects of carbon sources on PMLA production in flask , and the mechanism of carbon source on PMLA production was not explained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Manitchotpisit et al reported that most strains of A. pullulans in genetically diverse phylogenetic clades could produce PMLA. Ĉernáková et al found that A. pullulans could utilize a wide variety of carbon sources, such as d ‐xylose, lactose, sucrose, maltose, cellobiose, inulin, soluble starch, nonglycosidic substrates, etc. So far, there have been very limited publications available regarding the effects of carbon sources on PMLA production in flask , and the mechanism of carbon source on PMLA production was not explained.…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: DO, dissolved oxygen concentration; OAA, oxaloacetate; PEP, phosphoenolpyruvate; PMLA, β-poly(l-malic acid); TCA, tricarboxylic acid is a polymorphic fungus, well known as the producer of the commercial polysaccharide, pullulan, and other valuable bioproducts [5]. Recent work by Manitchotpisit et al [5] reported that most strains of A. pullulans in genetically diverse phylogenetic clades could produce PMLA.Ĉernáková et al [6] found that A. pullulans could utilize a wide variety of carbon sources, such as d-xylose, lactose, sucrose, maltose, cellobiose, inulin, soluble starch, nonglycosidic substrates, etc. So far, there have been very limited publications available regarding the effects of carbon sources on PMLA production in flask [7][8][9], and the mechanism of carbon source on PMLA production was not explained.…”
Section: Introductionmentioning
confidence: 99%